The Pascal’s Law of Physics Applied to Build a Reuse Material Robotic as Effective Physics Leaning Media - Korn Taksapattanakul; Arom Puteh; Ahamad Arun; Suchada Saengwiman (Universitas Riau, 2020)
The Pascal’s law is a part of physics subject which difficult for students to imagine and understand. Therefore, the aim of this work is to help the students to easily understand the Pascal’s law via studying the effect of fluid volume on movement joint mechanisms degree and applying to build a reuse material robotic as effective physics leaning media. The process start with teaching the students about the Pascal’s law. After that, encouraged the students to test the effect of fluid volume to each joint movement. Finally, they can assemble each component to build a movement robot. It was found that the students can understand the Pascal’s law after studied and analyzed the effect of fluid volume on join movement of each part of the robot. This knowledge helped student to build a robot that can successfully move by the Pascal’s law. Thus, this leaning media is an important development leaning skill of students about the Pascal’s law in physics.